Oliver Quick’s upward social mobility and the struggle for cultural recognition in Emerald Fennell’s Saltburn (2023): A sociological study - Indragiy Firzatulloh (Priviet Social Sciences Journal, 2026)
This study investigates the representation of Oliver Quick's upward social mobility and his struggle for cultural recognition in Saltburn (2023), directed by Emerald Fennell. Two research questions guide the analysis: (1) how is Oliver's upward social mobility represented in the film, and (2) how do cultural capital, habitus, and symbolic violence shape his mobility and negotiation of elite social space? Using Sorokin's (1927) theory of social mobility and Bourdieu's (1984) and Bourdieu's (1986) concepts of cultural capital, habitus, and symbolic violence, this study applies qualitative textual and cinematic analysis to examine dialogue, characterization, and visual elements such as framing, costume, and aspect ratio. The analysis identifies three interconnected phases of Oliver's mobility: Oxford as an institutional gateway that grants access without legitimacy, the Saltburn estate as a site of persistent symbolic exclusion enacted through everyday domestic ritual, and Oliver's strategic self-positioning through fabricated narratives and calculated manipulation, fully disclosed only in the film's closing montage. These findings are not merely isolated incidents but manifestations of the cultural and symbolic logic that governs entry into the elite British social space. The study concludes that Saltburn frames social mobility not as a meritocratic achievement but as a sustained struggle for cultural and symbolic legitimacy, in which recognition—understood through Bourdieu's (1990) concept of misrecognition rather than as simple elite acceptance—is granted only to those whose self-presentation is read as authentic rather than strategic.